Understanding Civil-Military Relations for better Civilian Control of the Military in Nepal - Rawal, Surendra Singh (Nepal Public Policy Review, 2022)
Conducive civil-military relations (CMR) is essential for political stability, good governance, and the country’s prosperity. However, there has been a misunderstanding or misinterpretation of this concept in some quarters in Nepal. The CMR is the relationship between the government and the military, especially the higher echelon of the officer corps, generally expressed as civilian control of the military. Good CMR is vital for national security and defence, which calls for organizing the military by balancing the societal and functional imperatives. While there are many existing theories in CMR, Nepal must focus on democratic civilian control as the country has embarked on a democratic political system. The features of democratic civilian control include division of authority between the state’s organs and the military, parliamentary oversight, subordination of the military to civil society, and maintaining the credibility and accountability of the military. This qualitative study concludes that the MOD is a crossroads where military expertise and civilian legitimacy intersect and establish a power relationship between democratically-elected civilian representatives and the military. The civilians must have authority and capabilities in determining the military’s policy issues, where the MOD and the legislatures must play an essential role in controlling and oversight the military. Specifically, the Parliamentary Defence Committee and the empowered Ministry of Defence must decide the military’s size, roles, higher-level promotion, budget, procurement, and foreign relations.